Flashover characteristics of G-11 at different cryogenic temperatures. (April 2019) - Li, J; Luo, L M; Huang, R J; Ma, J H; Liang, Y Q; Huang, C J; Wu, Z X; Shen, F Z; Wang, Y G; Xu, D; Liu, H M; Zhang, H; et al.
Abstract: The feeder busbar joint system is an important component in the International Thermonuclear Experimental Reactor (ITER) project. The insulation materials for the feeder busbar joint play a crucial role in both mechanical support and high voltage insulation. The G-11 block, which is a kind of industrial high-pressure, glass-reinforced epoxy laminates, has been chosen for the feeder busbar joint as insulation and mechanical support. The electrical characteristics of the G-11 depend significantly on temperature. As the feeder system works at the temperature of 77K, to ensure safe operation, the DC flashover voltage is required to be studied in a cryogenic environment. In this work, DC flashover characteristics of the G-11 at both room and cryogenic temperatures have been investigated using a self-developed test system. The results show that the surface flashover voltage rises as the flashover times increase. In addition, results indicate that the flashover voltage of the G-11 depends on orientations and it increases as the temperature decreases.